The potential yield of active play in the prevention of cancer. Issue 1 (2nd January 2017) - Block, Francesca; Gough, Aisling; Prue, Gillian; Solomon-Moore, Emma; May Kesten, Joanna; Smith, Lee
ABSTRACT: Literature has shown that participation in physical activity is associated with a reduction in the incidence of certain cancers. Physical activity levels across the life course are low. Since cellular damage from an inactive lifestyle accumulates over time, promoting physical activity from childhood is fundamental for cancer prevention. To date, interventions to promote physical activity in children have been unsuccessful over the long term. Physical activity can be accrued through several domains including sport and active play. Research suggests that sport participation and not active play tracks from childhood to adulthood. Active play may be easier to promote because it does not necessitate a certain level of skill or competency, and is enjoyable. The purpose of the present paper is to encourage more research into all areas of active play to increase population physical activity levels across the life course and thus aid in the prevention of specific cancers.